2018
DOI: 10.1371/journal.pone.0190213
|View full text |Cite
|
Sign up to set email alerts
|

General anesthetics cause mitochondrial dysfunction and reduction of intracellular ATP levels

Abstract: General anesthetics are indispensable for effective clinical care. Although, the mechanism of action of general anesthetics remains controversial, lipid bilayers and proteins have been discussed as their targets. In this study, we focused on the relationship between cellular ATP levels and general anesthetics. The ATP levels of nematodes and cultured mammalian cells were decreased by exposure to three general anesthetics: isoflurane, pentobarbital, and 1-phenoxy-2-propanol. Furthermore, these general anestheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 22 publications
2
30
0
1
Order By: Relevance
“…Support for this hypothesis is more than just conjectural. Many volatile and intravenous anaesthetics have been shown to depress mitochondrial function [7,8], disrupting the mitochondrial membrane potential and reducing intracellular ATP levels [9]. In fact, anaesthetics have been proposed as pharmacological probes for investigating mechanisms of mitochondrial uncoupling [10].…”
Section: Introductionmentioning
confidence: 99%
“…Support for this hypothesis is more than just conjectural. Many volatile and intravenous anaesthetics have been shown to depress mitochondrial function [7,8], disrupting the mitochondrial membrane potential and reducing intracellular ATP levels [9]. In fact, anaesthetics have been proposed as pharmacological probes for investigating mechanisms of mitochondrial uncoupling [10].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the molecular effect of individual non-ligand binding residues upon the binding affinity may facilitate the prediction of affinities of the ε subunit from different organisms based on sequence comparison. In addition, an improved knowledge of non-binding residues that nevertheless influence the ligand binding affinity may help to fine-tune genetically encoded ATP sensors, based on subunit ε ( Imamura et al, 2009 ; Yaginuma et al, 2014 ), which have been shown to be applicable to various medical and biological problems, such as measurement of intramitochondrial ATP concentration during hypoxia ( Kioka et al, 2014 ), the mechanism of anaesthetics on mitochondrial ATP synthesis ( Kishikawa et al, 2018 ) or the quantification of ATP levels of living cells infected by a virus ( Ando et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the alternative proposal can be made that the anesthetic suppression of cerebral metabolic rate could be, at least in part, to due to a direct inhibition of mitochondrial energy production. In line with this proposal, Kishikawa et al, recently found that three distinct anesthetics, isoflurane, pentobarbital, and 1-phenoxy-2-propanol (a non-clinical agent) could all abolish mitochondrial membrane potential, resulting in an inhibition of mitochondrial adenosine triphosphate (ATP) synthesis (Kishikawa et al, 2018). Consequently, we were interested in the question if metabolic suppression itself may reproduce at least some of the well-known electrophysiological effects of general anesthesia.…”
Section: Introductionmentioning
confidence: 91%
“…Anesthetics affect on the mitochondrial respiratory chain or its structure, such as an inhibition of respiratory complex I or II, with decreased mitochondrial ATP production (La Monaca and Fodale, 2012). Moreover, a recent study demonstrates that the inhibition of mitochondrial ATP synthesis can result from abolished mitochondrial membrane potentials under the effects of anesthetics (Kishikawa et al, 2018). Therefore, in the model we modulated , which is the inverse of the ATP production rate of a single neuron, so that the neurons have a larger at a deeper level of anesthesia.…”
Section: Model Neuronmentioning
confidence: 99%
See 1 more Smart Citation